Meningkatkan Motivasi Belajar Peserta Didik Melalui Model Pembelajaran Problem Based Learning Berbantuan Multimedia Interaktif - Rahman, Hardianto; Faisal, Muhammad; Syamsuddin, Afdhal Fatawuri (Jurnal Pendidikan Dasar dan Keguruan, 2024)
The objectives of this research are to describe the implementation of the Problem-Based Learning (PBL) model assisted by interactive multimedia media at Sekolah Dasar Negeri 69 Balang-balang and to enhance students' learning motivation through the implementation of the Problem-Based Learning (PBL) model assisted by interactive multimedia media at Sekolah Dasar Negeri 69 Balang-balang. The research method used is action research by adopting the STAR approach (Situation, Challenge, Action, Result Reflection, and Impact). Data were collected through teacher reflection journals, video recordings of lessons, observation sheets by school supervisors, interviews with students and teachers, surveys of students, and student learning artifacts. The results of this research indicate that this innovative approach has a significant positive impact on students' learning motivation in elementary school. Some key findings that can be drawn as the main conclusions include: 1) increased student engagement; 2) interactive multimedia can be an effective tool to facilitate concept understanding; 3) improving technology infrastructure is key to ensuring smooth implementation and seamless learning experiences; 4) students find learning with multimedia more enjoyable and engaging; 5) increased student motivation and participation through the PBL model assisted by interactive multimedia successfully stimulated students' learning motivation; 6) the indicators of successful implementation are met.